HIV infection and domestic smoke exposure, but not human papillomavirus, are risk factors for esophageal squamous cell carcinoma in Zambia: a case–control study. (30th January 2015) - Kayamba, Violet; Bateman, Allen C.; Asombang, Akwi W.; Shibemba, Aaron; Zyambo, Kanekwa; Banda, Themba; Soko, Rose; Kelly, Paul
<x xml:space="preserve">Abstract</x> Human immunodeficiency virus (HIV) infection and exposure to domestic and cigarette smoke are risk factors for esophageal squamous cell carcinoma. Human papillomavirus (HPV) infection does not appear to explain this relationship with HIV. HPV immunization is unlikely to prevent the apparent increase in esophageal cancers in young Zambian adults. <boxed-text content-type="graphic" id="cam4434-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>